Fixing Windows XP Annoyances - Karp, David A. (O'Reilly, 2011)
Windows XP is the most popular operating system on the planet--and the most annoying. From incomprehensible error messages to inexplicable crashes, from wonky wireless setups to just finding a file, Windows can make your computing life a nightmare. But thanks to Fixing Windows XP Annoyances, you can banish the bugs, speed up operations, and just make Windows work right.